The Effect of Occupational Safety, Work Skills, And Employability on Stress and Implications on The Productivity of Employment Construction Service Workers - Nurhani; Wibowo; Budi Santoso (Journal of Business and Behavioural Entrepreneurship, 2020)
This study aims to analyze the effect of occupational safety, work skills, and employability on stress and its implications on the labor productivity of construction service workers in Jabodetabek. This researcher uses a quantitative approach with a survey method. The sample used in this study are 303 permanent workforce in the construction service sector of structure work ( formwork, putting ironn and casting ) who have a minimum of high school education equivalent that determines proportionate random sampling. The research data were obtained from distributing questionnaires and analyzed using Structural Equation Modeling (SEM) analysis supported by descriptive statistical analysis. The results of this study indicate occupational safety, work skills, employability and stress have a direct effect on work productivity; occupational safety, work skills and employability have a direct effect on stress; occupational safety, work skills and employability have a indirect effect on work productivity with stress mediation. Therefore, improvements in occupational safety, work skills, employability, and stress can increase work productivity. The novelty of this study is in the form of a research model of the effect of occupational safety, work skills, and employability on work productivity with stress mediation developed from previous relevant studies with construction service research locations in Jabodetabek, 2019.